Promoting effects of soil C and N and limiting effect of soil P jointly determine the plant diversity during the aerial seeding restoration process in Mu Us sandy land, China - Gong, Xiaoqian; Qi, Zhimin; Wen, Jia; Yan, Yongzhi; Liu, Qingfu; Li, Yuanheng; Zhang, Qing (Frontiers in Plant Science, 2023)
Exploring the change and maintaining mechanism of plant diversity is of great significance for guiding the restoration of degraded ecosystems. However, how plant taxonomic, functional, and phylogenetic diversity change during long-term ecosystem restoration process and their driving factors remain unclear. Based on the 35-year time gradient of aerial seeding restoration in Mu Us sandy land, this study explored the changes in plant taxonomic, functional, and phylogenetic diversity and the driving factors. The results showed that plant taxonomic, functional, and phylogenetic diversity showed consistent response with the aerial seeding restoration, all of which increased first and then tended to a saturation state in the middle of restoration (14 2 years). TN, TOC, and NO3 –N increased with aerial seeding restoration and showed a significant positive correlation with plant diversity of the three dimensions, while AP showed a negative correlation. Soil nitrogen and carbon promoted the increase of diversity of three dimensions in the early restoration period, while phosphorus limited the increase of diversity of three dimensions in the middle and late restoration periods.The diversity of three dimensions was mainly affected by restoration time, soil nutrients, and climate factors, and the coupling effect of restoration time and soil nutrients was dominant. These findings indicate that the plant diversity in different dimensions and soil nutrients are improved by aerial seeding restoration. Our study highlights that aerial seeding restoration mainly improves plant diversity by increasing soil nutrients, and the relative effects of different soil nutrients on plant diversity during restoration are inconsistent.